The internet, news consumption, and political attitudes - Che-Yuan Liang; Mattias Nordin (Uppsala University, Department of Economics, 2012)
We investigate the effects of the rise of the Internet as an additional mass medium on news consumption patterns and political attitudes. We use Swedish survey data from 2002 to 2007, the period during which online news media emerged. We find that broadband access is associated with online media consumption which, to some extent, crowds out offline consumption. Furthermore, these altered news consumption patterns have no or small effects on political attitudes.
urn:nbn:se:uu:diva-181992
Keywords: D72; D83; 330; news; the Internet; political attitudes; Kommunikationsmedien; Internet; Meinung; Schweden